Breaking bad news in China – the dilemma of patients' autonomy and traditional norms. A first communication skills training for Chinese oncologists and caretakers. Issue 5 (27th May 2012) - Wuensch, Alexander; Tang, Lilli; Goelz, Tanja; Zhang, Yening; Stubenrauch, Sara; Song, Lili; Hong, Ye; Zhang, Haiwei; Wirsching, Michael; Fritzsche, Kurt
Abstract Objective Current practice of breaking bad news in China involves disclosure of information first to family members who then decide whether the patient should receive this information. Recently, however, patients' right to be informed has been regulated by law. This represents a dilemma for oncologists who now have to balance traditional practice with new legal requirements. A communication skills training (CST) was developed for Chinese practice. It addresses this issue and may help participants find individual solutions within these conflicting requirements. Methods A first CST about breaking bad news took place at the Beijing Cancer Hospital, China, with 31 participants. We (i) assessed current practice, (ii) evaluated the workshop and (iii) self‐assessed performance ratings about breaking bad news before and after the workshop with the help of questionnaires. Results (i) Participants stated that in most cases (78%), they inform family members first. Contrary to this practice, participants think that about 75% of patients would like to be informed first, independent of family. (ii) Overall, the workshop received a very good rating (M = 1.2; scale between 1 and 6). (iii) After the workshop, the participants rated their performance significantly higher in all areas, for example, talking about diagnosis, prognosis and death with the patient and the family. Conclusions The CST showed high acceptance and led to significantly improved performance ratings of participating physicians in many areas. It helped participants deal with conflicting demands. For future trainings, further socio‐cultural adaptations are needed. Obvious conflicts still exist and need to be resolved. Copyright © 2012 John Wiley & Sons, Ltd.